Tongue microstructure physically constrains division of labor in bumblebee foraging - Zexiang Huang; Shumeng Wu; Qinglin Wu; Tianyu Mai; Jieliang Zhao; Bo Wang; Jianing Wu (Proceedings of the National Academy of Sciences, 2026)
Bumblebee ( Bombus terrestris ) is a primitively eusocial species that sustains its colonies by dividing foraging duties between queens and workers. Previous research emphasizes hormonal, metabolic, and behavioral contrasts between the castes but seldom considers why queens relinquish foraging once workers emerge. Here, we link foraging efficiency to tongue microstructure, providing physical evidence for the shift in bumblebee foraging behavior.